Phage display identified peptide with selectivity for human osteoarthritic chondrocytes - Martins, Ivone M. (2023)
Osteoarthritis (OA) is one of the most common joint disorders in western populations, affecting millions of people worldwide and with a rising incidence as life expectancy continues to increase. Current therapies for OA management fail to halt the progressive degradation of articular cartilage, urging the need for more effective therapies to improve cartilage function and enhance patient's quality of life. Through phage display technology, biopanning on a population of heterogenous chondrocyte cells isolated from six different OA donors, and using a random 12-amino acid peptide phage library, a peptide selective for human OA chondrocytes (GFQMISNNVYMR) is identified. A twofold increase in fluorescence intensity is observed for OA chondrocytes, compared to normal chondrocytes, when cells are incubated with the identified peptide conjugated to a fluorescent label, being selectively internalized by OA cells. The identified peptide can be further modified and exploited for developing early diagnostic of OA and/or improve drug delivery to target cells through peptide-drug conjugates.